Development of the Value of the Role of the HKBP (Huria Kristen Batak Protestant) Church in the Development of Tolerance in Religious Life in the Community of Semarang City 2000-2010 in History Learning - Parulian, Ricky Putra (Universitas Negeri Semarang, 2017)
The purpose of this study was to determine (1) the history of HKBP Semarang, (2) the development of HKBP Semarang, and (3) HKBP's role in the development of religious tolerance Semarang 2000-2010. The historical method consists of collecting source/data, comparing the source with other sources, analysis, interpretation, and writing resources. The results of this study are: HKBP Semarang has a close relationship with other religions that exist in the surrounding area because not only the Protestant religion that is in the area of Semarang but also some people are Muslims, Hindus, Buddhists, and Catholics. Relationships between people, society, and the environment helping each other among religions will create an atmosphere of harmony among religions with no problem connecting beliefs, mutual tolerance between faiths when other people are doing religious activities, interaction with the environment, keeping all of what is on earth as a form of gratitude to God.